Genetic Susceptibility due to Moderate Breast Cancer Risk Gene CHEK2: a case report - Kankuri-Tammilehto Minna (JSciMedCentral, 2022)
Today we are increasingly interested in finding out the hereditary variants of moderate risk from a cancer patient. Multigene next generation sequencing (NGS) panel technology, massive parallel sequencing, can efficiently and economically analyze genes in 3 to 6 weeks. There are agreed criteria based on which to suspect hereditary breast cancer and thus to make a referral to clinical genetic unit. The topic research subject is to investigate the cancer risk associated with moderate risk genes. Appropriate follow-up recommendations for persons with moderate genetic susceptibility pathogenic variants to breast cancer are updated regularly as scientific research is published. This is a case report on two CHEK2 families in which pathogenic variant in CHEK2 gene does not alone explain the breast cancer risk of the patients. This is also a mini review of genetic susceptibility of CHEK2 moderate breast cancer gene.